Wolff Brothers: You Had Me at Wolf - Book 1 - Spear, Terry (Naperville, Illinois : Sourcebooks Casablanca, 2020)
"The hot, powerful Wolff brothers have moved to the outskirts of Silver Town and opened a ski lodge. Theyve always wanted to live in a wolf-controlled area, and now they have their chance. Theyre settling in for a quiet winter, when their lives suddenly become way more exciting than theyd ever planned. Private Investigator and gray wolf shifter Josie Grayson is hot on the trail of a dangerous criminal hiding out at the ski lodge when her partner takes ill and must leave her to pursue the mission alone. Blake Wolff steps in--he cant resist the allure of this brilliant and focused she-wolf whose presence awakens a long dormant yearning in his heart. As pursuit of their quarry heats up, Blake has a mission of his own...to convince Josie that theres more to life than work...and that shes his perfect mate."--Provided by publisher.
Keywords: Man-woman relationships -- Fiction; Shapeshifting -- Fiction; Werewolves -- Fiction; Private investigators -- Fiction; Paranormal fiction; Detective and mystery fiction; Romance fiction